Reuse of mining waste as aggregates in fly ash-based geopolymers. (20th May 2019) - Capasso, I.; Lirer, S.; Flora, A.; Ferone, C.; Cioffi, R.; Caputo, D.; Liguori, B.
Abstract: Mineral production continues to be necessary for economic development, consequently also the management of mining and mineral-processing wastes represent a considerable issue in terms of recycling and economic strategies for the future. One of the most promising reuses for coarse-grained mining wastes, especially barren waste rocks from coal and metal mining, is their application in the building and construction sector. An experimental research has been developed with the aim of studying the possible reuse of waste rocks – coming from mining activities-as fine aggregates in a fly ash based geopolymer: physical, chemical and mechanical tests have been carried out in order to analyze in detail the interaction between the geopolymer binder and the rock waste aggregates. All the mixtures, characterized by an aggregate/binder/ratio ranging between 0.05 and 1, showed a final microstructure characterized by a rather homogeneous geopolymer matrix embedding the mining waste rock. The geopolymeric matrix governs the overall mechanical behavior of the system, thanks also to the strong interaction at the interface between matrix and aggregates (mining waste). Moreover, all the geocomposites satisfy the prescribed limit for inert or non-hazardous waste. Highlights: The most promising reuses for mining wastes, and especially waste rocks are as building and construction materials. Waste rocks coming from mining and quarrying activities were used in the production of environmentally friendly geopolymers. The nature of the waste rock promoted a continuous interface between geopolymeric matrix and aggregates. The strong interaction between binder and mining waste is responsible of the mechanical performances of the geo-composites.